The incentive effects of higher education subsidies on student effort - Aysegül Sahin (Federal Reserve Bank of New York, 2004)
This paper uses a game-theoretic model to analyze the disincentive effects of low-tuition policies on student effort. The model of parent and student responses to tuition subsidies is then calibrated using information from the National Longitudinal Survey of Youth 1979 and the High School and Beyond Sophomore Cohort: 1980-92. I find that although subsidizing tuition increases enrollment rates, it reduces student effort. This follows from the fact that a high-subsidy, low-tuition policy causes an increase in the percentage of less able and less highly motivated college graduates. Additionally
Keywords: D64; D82; I21; I28; 330; and potentially more important; Studienfinanzierung; Leistungsanreiz; Bildungsverhalten; Studierende; Schätzung; USA